PURIFICATION OF CRUDE GLYCEROL BY SHORT PATH EVAPORATION. THEORETICAL AND PRACTICAL ANALYSIS OF PROCESS PARAMETERS - TRIFOI, Ancuța Roxana; CRUCEAN, Augustin; STĂNULEȚ, Lucica; BLĂJAN, Olimpiu; AGACHI, Paul-Şerban (Studia Universitatis Babeș-Bolyai Chemia, 2015)
Crude glycerol, the by-product from biodiesel production process, increased drastically as rapid growth of biodiesel industry. This by-product contains many impurities such as water, soaps, free fatty acids, esters etc. This paper presents a process development based on molecular distillation or short path evaporation, for glycerol purification up to 99%. Several experiments and theoretical analysis have been carried out to identify the effect of important parameters (mean free path, Knudsen number, evaporation rate, feed flow rate and evaporation temperature) which determine the performance of the molecular distillation process. The purified glycerol is collected in the distillate while the residue is enriched in higher molar mass components. High performance liquid chromatography (HPLC) was employed to determine the purity of glycerol.